Long-term outcomes in health-related quality of life influence chronic disease management in patients with pulmonary hypertension - Li, Jin-Ling; Xiao, Fan; Liu, Hong-Ting; Li, Hui-Ting; Zhao, Qin-Hua; Sun, Chun-Yan; Zhu, Yan; Yan, Lei; Wang, Wen-Yue; Luo, Hui; Gong, Su-Gang; Jiang, Rong; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Significantly improved survival in patients with pulmonary hypertension (PH) has raised interest in maintaining a good quality of long-term survivorship. In this study, health-related quality of life (HRQOL) measurement was used to assess the long-term changes of physical and mental outcomes. Methods: The 559 consecutive inpatients with PH, completed generic HRQOL (Short Form-36) when diagnosed PH with right heart catheterization. Assessments took place at short-term (1 year), mid-term (3 years) and long-term (5 years) follow-up. Results: Patients with PH suffered severe impairments in both physical and emotional domains compared with those of U.S. population normative values. Patients with PH due to chronic lung disease have the worst physical component summary (PCS), but there was no difference in mental component summary (MCS) among different PH types. Reduced PCS was correlated with WHO FC severity and pulmonary vascular resistance (PVR). Z score showed that the changing trend of mental condition continuously declined from baseline to midterm and long-term follow-up, but PCS seemed to be stable or improved. Cox regression analysis indicated increased baseline PVR, WHO FC III and IV, decreased physical subscale of role-physical, mental subscale of social-functioning and MCS has increased risk of mortality in long-term follow-up. Conclusions: PH patients have poor HRQOL. The long-term change of physical status seemed to be stable, but the mental state was continuously worse. These suggested identifying and intervening mental health progresses is a noteworthy issue in PH chronic management.